Why Do Banks Go Abroad? - Evidence from German Data - Claudia M. Buch (Kiel Institute of World Economics (IfW), 1999)
This paper provides empirical evidence on the determinants of foreign activities of German banks. We use regionally disaggregated panel data for the years 1981?98 and distinguish foreign direct investment from total foreign assets of domestic banks, of their foreign branches and their subsidiaries. Foreign activities are found to be positively related to demand conditions on the local market, foreign activities of German firms, and the presence of financial centers. This supports the hypothesis that German banks follow their customers abroad. Exchange rate volatility has some negative impact. EU membership and the abolition of capital controls seem to have exerted a greater influence on foreign assets than on FDI of German banks, thus weakly supporting the hypothesis that the two are substitutes.
Keywords: F21; F23; G21; 330; foreign activities of commercial banks; Germany; panel cointegration; Bank; Multinationales Unternehmen; Direktinvestition; Deutschland